Vibration of sandwich beams with 2 non-overlapping delaminations - Yip, Kok Seng. (2009)
One of the commonly encountered types of defect in laminated composite structures is delamination. Delamination not only affects the strength and integrity of the structure by contributing to its final failure but also causes a reduction in stiffness, which affects its dynamic behavior.